The seeds of exchange bear fruit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Organising seed shows and contests with attractive prizes are a good way to encourage farmers to save, select and exchange seeds, as shown by the Intermediate Technology Development Group (ITDG) - East Africa. The Group has helped two communities in...